Geographic and Racial Disparities in Infant Hearing Loss. (December 2018) - Lantos, Paul M.; Maradiaga-Panayotti, Gabriela; Barber, Xavier; Raynor, Eileen; Tucci, Debara; Hoffman, Kate; Permar, Sallie R.; Jackson, Pearce; Hughes, Brenna L.; Kind, Amy; Swamy, Geeta K.
Objective: Approximately 1 to 2 of every 1000 American newborns has hearing loss identified by newborn screening. This study was designed to determine if infant hearing loss is more common in socioeconomically disadvantaged communities. Study Design: In this retrospective study, we analyzed electronic medical record data using geostatistical models. Setting: Infants were residents of Durham County, North Carolina, born in 2 hospitals of the Duke University Health System. This county includes the city of Durham and surrounding suburban and rural communities. Subjects and Methods: Subjects were hearing-screened newborns, born between 2005 and 2016, whose residential address was in Durham County, North Carolina. This was a retrospective study using medical record data. We used Bayesian regression models with smoothing of coordinate date to identify both spatial and nonspatial predictors of infant hearing loss. Results: We identified 19, 348 infants from Durham County, of whom 675 had failed initial hearing screening and 191 had hearing loss confirmed on follow-up. Hearing loss was significantly associated with minority race (odds ratio [OR], 2.45; 95% confidence interval, 1.97-3.06), as well as lower gestational age and maternal sexually transmitted infections. We identified significant geographic heterogeneity, with a higher probability of hearing loss in poorer urban neighborhoods (local OR range, 0.59-1.39). Neighborhood disadvantage was a significant predictor of hearing loss, as was high local seroprevalence of cytomegalovirus (CMV) among pregnant women. Conclusions: Urban, low-income neighborhoods have a high prevalence of infant hearing loss compared with more affluent surrounding communities, particularly among minorities. This distribution may be attributable to congenital CMV infection.